The dose-response relationship of fruit and vegetable intake and risk of type 2 diabetes among rural China: The Henan Rural Cohort study. Issue 2 (April 2023) - Niu, Kailin; Lyu, Quanjun; Zhang, Shuhua; Wang, Chongjian; Mao, Zhenxing; Cui, Songyang; Gu, Ruohua; Li, Linlin
Abstract: Aims: To explore the dose-response relationship of fruit and vegetable (F&V) intake and type 2 diabetes (T2D) risk in rural China. Methods: A total of 38798 adults were recruited from the Henan Rural Cohort Study. F&V intake was assessed by a validated food-frequency questionnaire. Logistic regression and restricted cubic splines analysis were conducted to calculate the odds ratio (OR) for T2D relative to F&V intake and investigate the dose-response relationship. Results: Higher intake of fruit or combined F&V was in connection with a lower risk of T2D, after adjusting for multiple confounders. After analyzing the dose-response relationship, we found that the odds of T2D decreased significantly with fruit consumption ≥ 260 g/day or F&V intake between 600 and 1000 g/day. And in subgroup analysis, we found that the negative correlation between fruit consumption and T2D was more pronounced in non-current smokers and non-current drinkers. Conclusions: High intake of fruit alone or combined F&V is related to a reduced risk of T2D in rural China. Fruit intake ≥ 260 g/day and total F&V consumption of 600–1000 g/day should be encouraged to promote good health. Highlights: It investigated the dose-response relationship between F&V and T2D in rural China. Individuals should be encouraged to consume ≥ 260 g of fruit per day. Individuals who intake high fruit plus do not smoke or drink perhaps profit the most. Total F&V consumption of 600–1000 g/day should be encouraged to promote good health.